Opportunities for Backing and Restoration of Business Information - Denchev, Emil (Research Papers, 2009)
In the paper, the topics, associated with the business information protection, are viewed. It is the goal to clear, how by making a ongoing magnetic archive the protection is realized from destroying more technical reasons, what the opportunities for this are, as lending as well how this for optimizing the work of the employees from the company, as time and fiscal means. In the present composition the following possibility - making archive by copying information, making archive by using program tools and online archiving web server of data are included. The advantages and the demerits of each one of these opportunities are viewed, as he is accepting to online the backup. The statement is illustrated with practical cases, the opportunities for online backing their business information in the site xdrive.com gain the performance to which it will permit the users to make a consumer’s account as well.